GENERAL AND ADMINISTRATION EXPENSES ALLOCATION TECHNIQUE BY MARATHHON INDONESIA, AN OIL AND GAS COMPANY - IN COMPARISON WITH PRODUCTION SHARING CONTRACT (PSC) REQUIREMENTS - Pratama, Indra (Academic Research Centre Services, 2013)
This study is descriptive explaining the development of the new General and Administration technique in relation with allocation of expenses into several Production Sharing Cost (PSC). From the observation done by the researcher it was shown that the general and administration technique Project Admin (Drilling and Exploration Departments) from Support Admin (Non-Drilling and Exploration Departments) as required by SKKMIGAS. Moreover, SKKMIGAS also required the time to be allocated usin man-hours. This has also been achieved by the new Marathon procedure. Marathon even made further innovations, by designating only several Departments need to be time-writers. The non time-writers will be allocated according to the result of the time-writers. this is useful in order to provide better information regarding the work for each  concession. Therefore, the new method has fulfilled SKKMIGAS requirements and is also in line with the ring-fence policy